Role of macrophage colony-stimulating factor (M-CSF) in human granulosa cells. (1st December 2016) - Xu, Song; Zhang, Zhifen; Xia, Li-Xia; Huang, Jian
Abstract: Macrophage colony-stimulating factor (M-CSF) has been proved to have a positive role in the follicular development. We investigated its effect on human granulosa cells and found that M-CSF could stimulate the production of E2 . The production of FSH receptors was enhanced by M-CSF in vitro in a dose-dependent manner with or without the addition of tamoxifen ( p  <0.05). Correspondingly, FSH was also able to coordinate the expression of M-CSF and its receptor ( p  <0.05). That maybe important to maintain the level of Nppc and the meiotic arrest of the oocyte. The protein p-JAK2 and p-STAT3 in JAK/STAT-signaling pathway elevated after the influence of M-CSF ( p  <   0.05). These results suggest that M-CSF has a role in regulating the response of granulosa cells to gonadotropins. Its function is associated with JAK/STAT-signaling pathway.